Nitrogen management sensor optimization, yield, economics, and nitrogen use efficiency of different wheat cultivars under varying nitrogen levels - Kumar, Bipin; Shaloo,; Bisht, Himani; Meena, M. C.; Dey, Abir; Dass, Anchal; Paramesh, Venkatesh; Babu, Subhash; Upadhyay, Pravin Kumar; Prajapati, Vijay Kumar; Chandanshive, Aniket; Suna, Truptimayee; et al. (Frontiers in Sustainable Food Systems, 2023)
The excessive application of nitrogen in wheat cultivation results in substantial decreases in yield, limited economic gains, and causes adverse environmental consequences. Excess nitrogen use in wheat poses major yield penalty and poor economic returns besides several negative environmental impacts. In this study, the main objective is to assess and optimize the values of different nitrogen-assessing tools at varying levels of Nitrogen for three wheat cultivars. Three non-destructive sensing devices; Leaf color chart (LCC), SPAD, and GreenSeeker were optimized at four three levels different of nitrogen doses (0 kg N ha -1 , 90 kg N ha -1 , 120 kg N ha -1 , and 150 kg N ha -1 ) in three wheat cultivars viz HD 2967, HD 3059, and HD 3086. Results indicated that at 60 days after sowing (DAS) the optimum values of LCC, SPAD and GreenSeeker were 4.17, 0.62, 44.2, at flag leaf stage were 4.12, 0.60 and 43.8, respectively and this could be achieved at 120 kg N ha -1 with grain yield of 4.87 t ha -1 . At 120 kg N ha -1 , considerably better gross return (Rs. 97444.4), net income (Rs. 66681.4), and B:C ratio (2.2) were obtained. The highest Agronomic efficiency of N (21.2%) was recorded at 120 kg N ha -1 while, the N uptake and recovery (129 kg ha -1 and 59.2 %) were significantly higher at 150 kg N ha -1 . We can conclude that optimized values of these sensors at different doses of N would be better guidance for precision N management that may reduce the input cost, maximize return and minimize the N losses in wheat.